EXTRACT PREPARATION OF MAJOR FOOD ALLERGENS OF PAKISTAN AND THEIR PROTEIN PROFILING - K. Zahra; S. Rehman; N. Javed; M. S. Aslam 2and Z. Abbas1 (Journal of Animal and Plant Sciences, 2019)
Food born antigens induce helper T-cells to produce immunoglobulin IgE leading to food allergies. Allergic extracts of common foods such as cow milk, buffalo milk, peanut, egg yolk and egg white and wheat were prepared using different methods. Protein concentration was determined by Bradford assay in which buffalo and cow milk curd showed maximum concentration of 29.6 and 27.7mg/ml respectively. Protein extracts of different foods were resolved on 12% SDS-PAGE. In buffalo and cow milk two proteins having a molecular weight of 18.4KD and 14KDa were identified as β-lactoglobulin and α-lactoglobulin by comparing with Allergen Nomenclature WHO/IUIS. Similarly, Ara h 1 allergen having 64KDa molecular weight was identified in peanut extract. Oval-albumin having 43kDa was identified in egg white and egg yolk contains α-levitin and YGP42 with 70-80 KDa and 35-40 KDa molecular weights respectively. Water soluble gliadins such as α, β, у,ω components and alcohol soluble gluteinins were found in wheat extract. The current study about protein profiling of major food allergen will help to identify clinically significant food allergens in local population by their cross reactivity with allergic patient sera. The identified local allergens will contribute in the diagnosis and management of food allergy.
Keywords: N/A